UPAYA ISOLASI β-ASARONE PADA EKSTRAK n-HEKSAN RIMPANG DRINGO (Acorus calamus L.) ASAL KABUPATEN PINRANG - Siti Sya'diyah; Risda Waris; Ahmad Najib (Faculty of Pharmacy, Universitas Muslim Indonesia, 2014)
The isolation of n-hexane extract from Sweet Flag rhizome (Acorus calamus L.) was done. The aim of this research is to obtain β-asarone isolate as marker compound of Sweet Flag (Acorus calamus L.). Sample from 1 kg of dried rizhome, mascerate using n-hexane. This process produce 31 ml thick extract. Isolation of n-hexane extract using column chromatography with isocratic methode using n-hexane etil acetat 8 : 2. The isolate identified by UV-Vis spectroscopy, IR spectroscopy, (1H) NMR and Gas Chromatography Mass Spectro. From the data result show that isolate is β-asarone.